The Archaeology of Buddhism in the Maldives : Excavation of a Buddhist Monastery at Kaashidhoo - Mikkelsen, Egil, (Asian Studies E-Books Online, Collection 2025., 2025)
Part of a Buddhist monastery dating to A.D. 200-1500 was excavated between 1996 and 1998 on the island of Kaashidhoo in the Maldives, uncovering extensive ruins and human graves. This book compares the findings with those from monasteries elsewhere in Asia, investigating the spread of cowrie shells, Chinese stoneware and South Asian earthenware. It documents all known Buddhist sites, sculptures and artefacts in the Maldives, presenting new evidence of Buddhist life, religious behaviour, funerary practice, faunal history and trading networks. The book offers a fresh interpretation of the conversion from Buddhism to Islam in the Maldives.